Unconventional views on inflation control: Forward guidance, the Neo-Fisherian approach, and the fiscal theory of the price level - Peter Spahn (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
In recent years, various "unconventional" views have been advanced that promise to offer new analytical insights and policy approaches that are suited to control the value of money, particularly in a constellation of low growth and unemployment. Whereas Forward Guidance attempts to decrease the real interest rate by low nominal rates and by creating excessive inflationary expectations, the Neo-Fisherian approach suggests to increase nominal rates immediately to the long-run equilibrium value that corresponds to the inflation target. The Fiscal Theory of the Price Level believes that goods prices jump to a level that validates the long-run sustainability condition of government debt. All three views are criticized for analytical and empirical reasons.
urn:nbn:de:bsz:100-opus-14643
Keywords: E52; E58; 330; interest rate policy; zero-lower bound; low-growth equilibrium